Present and future of Photovoltaics in Czech Republic from the point of view of a large power utility company - Burianová, Eva (2011)
Goal of this thesis is to analyse sequence of events that led to current situation on the solar market in Czech Republic. Based on this analysis, current situation and scenarios for the near future from the point of view of large power utility company are described. For this aim, analysis of macro-environment is employed and focuses in detail on legislative and technological factors. Definition of possible scenarios starts with the description of current situation of saturated market. Solar power plants are then presented as reasonable equity investment from the point of view of large power utility company. Assumptions and entry data are described and the investment is evaluated using the net present value evaluation tool. For chosen entry parameters, sensitivity analysis is performed. This thesis then defines the situation when electricity produced from solar irradiation becomes competitive with other conventional sources.